STRATEGI PENGEMBANGAN MASYARAKAT MELALUI PROGRAM PEMBUATAN COCOMESH DI RUMAH KREATIF SRIWIJAYA KOTA LAHAT (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze community development strategies through the cocomesh production program at the Sriwijaya Creative House in Lahat City using a qualitative case study approach. The research subjects consisted of five purposively selected informants. Data were collected through interviews, observation, and documentation, and analyzed through data reduction, presentation, and conclusion drawing. The results indicate that the empowerment process was carried out through outreach, training, mentoring, and direct practice, with a high level of community participation in production and marketing. This program had a positive impact on increasing income and strengthening the community's social aspects. Supporting factors included the availability of raw materials and institutional support, while barriers included limited equipment and market access. Overall, this program was quite effective in increasing community capacity but still requires institutional and marketing strengthening for sustainability